Achieving Job Satisfaction through Spirituality: A Case Study of Muslim Employees - Ashar Awan; Nisar Hamdani (International Journal of Islamic Economics and Finance Studies, 2015)
The present study explores the role of spirituality in achieving job satisfaction. Divine Economics Framework is used for quantifying the interrelationships between spirituality and worklife using empirical data of 383 workers from 5 districts of Azad Kashmir. The study analyzed the effect of spirituality level of workers on their subjective evaluation of their worklife (job satisfaction). An index of workers' spirituality is developed using Principle Component Analysis (PCA). The literature on theology and philosophy indicates that spirituality has many types which may lead to produce a systematically different human behavior. To test whether or not workers having different levels of spirituality have the same job satisfaction, Logistic regression technique is used. The results of given sample revealed that besides the conventional variables such as income, age, education, health, and job sector, a particular type of spirituality is a significant predictor of workers' job satisfaction. Our estimates relating to selected dimension of spirituality are presented to serve as new insights for further research in different types of spirituality at workplace. This study concludes that the Divine Economics Framework is relatively more capable to analyze economics of spirituality. The future research may utilize this framework to study the interrelationships of spirituality with workplace as well as other areas of economics
Keywords: 330; sprituality; wellbeing